Sejarah Pengajaran Bahasa Arab Sebagai Bahasa Asing - Salmah Intan (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2013)
Arabic language was originally from Semitic. Following the progress of Islamic mission, ArabIc language was significantly developing because of its uniqueness. Since Roman Empire to 20th century, the history of foreign teaching was signed by dialectic discource indicating emerges of a mathode as response to previous methods. Arabic teaching in this world was influnced by religous interest, further more it was affected by politics and sciences motives as well as human interrelation among countries. In Indonesia, Arabic language was introduced as respons to colonialism based on religious interest.